Analysis of Asset Management in Indonesia Amidst Black Swan Conditions - Fancha Alpha Sebayang Sebayang; Ardhani Sabdatama; Adella Kurnia Sari (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted to analyze asset management in the government when it is in the midst of a condition of uncertainty (black swan) in terms of efforts to restore and support economic growth in Indonesia. This research is qualitative in nature from the results of data processing in the central government in the management of State-Owned Assets. This research will produce recommendations for an asset procurement system which is an element of asset management related to systems for planning, budgeting, management, recording of valuation and management, management of the use and disposal of assets.